NUMERALS’ USAGE PROBLEMS IN LATGALIAN LANGUAGE - Bierzeņš, Aņss Ataols (Via Latgalica, 2012)
In the article is told about some actual problems with numerals which came up in Latgalian language after intensification of its’ usage in 90ties:1) to use or not to use a dot after ordinal numbers;2) to use an ordinal indicator „№“ or „Nr.“;3) how to decline the noun „gods“ ‘year’;4) how to write calendar dates.The author analyses a variety of sources: old Latgalian written texts – newspapers and calendars, spontanous dialectal speech, as well as solutions of these problems in other languages – mostly neighbor.The conclusions are:1) writing of ordinal numbers without a dot fits more to the Latgalian written tradition;2) traditionally the ordinal indicator „№“ was used and there are no serious reasons to move to an other designation;3) declination of the noun „gods“ should be discussed in a wider discuccion and in the context of nouns „ols“ i „mads“;4) looks that the usage of genitive of the name of the month and adding of noun „dīna“ ‘day’ at the end is more traditional form of representation of calendar date.